A Cognitive Theory of Reasoning and Choice - Pedro Bordalo; Nicola Gennaioli; Giacomo Lanzani; Andrei Shleifer (The Quarterly Journal of Economics, 2026)
Abstract We present a theory of choice in which attention to the features of options is determined by the decision maker’s categorization of the current problem in a set of problems she solved in the past. Categorization depends on goal-relevant and contextual problem-level features. The model yields heterogeneity in attention and choice in a given problem based on different past experiences and instability when changes in irrelevant context cause recategorization. We show that heterogeneous and unstable representations of a choice problem unify major biases in judgment and decision making.